PP88 Economic Impact Of New Diagnostic Tools In Severe Sepsis - Neeser, Kurt; Oelze, Ilse-Barbara; Müller, Elvira (International journal of technology assessment in health care, 2019)
Copyright © Cambridge University Press 20192019Cambridge University PressIntroductionConstantly rising healthcare costs and the increasing incidence of antimicrobial resistance represent a growing burden on public health, affecting patients, physicians, payers, and health authorities. This analysis assessed the economic impact of improved diagnostic accuracy among septic patients.MethodsA cost-consequence model was developed to evaluate two different scenarios for the treatment of severe sepsis: scenario one represents the current status of diagnostic performance used for an antimicrobial treatment; scenario two is based on the assumption that a more accelerated diagnostic process results in 15 percent more patients being treated with an efficient antimicrobial drug early in their therapy. Data for the average patient-related cost for diagnostics (EUR 1,182) and overall cost (EUR 12,090), length of hospital stay (average 18.7 days), and number of patients affected annually (n = 771) were derived from the German Diagnosis-Related Group Catalog for 2017. Further, the impact of optimal versus inadequate therapeutic approaches on length of hospital stay (38% decrease), hospitalization cost (40% decrease), and mortality rate (28% decrease) were derived from published sources.ResultsBy using more efficient tests to enable earlier detection of sepsis in patients who otherwise would not receive appropriate treatment, 36 additional patients were appropriately treated. The overall annual length of hospital stay can be shortened by 319 days and the number of sepsis-related deaths reduced by three. The overall annual costs in scenarios 1 and 2 amounted to EUR 11.4 and EUR 11.2 million, respectively. The main savings resulted from reduced expenses for hospital stay, drugs, readmissions, and progression to septic shock.ConclusionsIncreasing cost pressure and the rise in multi-resistant germs are a burden, which will increase over the next decade. The present analysis showed that a willingness to intervene early and stop detrimental developments, and to invest in effective technologies, can promote affordable health care.